Pengaruh Sampah Plastik Terhadap Kelimpahan Semai Mangrove di Tambak Wedi Surabaya - Megawati Mutiara Gusti; Nirmala Idha Wijaya; Mahmiah (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2022)
One of the habits of the people that are difficult to get rid of is throwing garbage. The trash the community throws away will be exposed to seawater during high tide and spread widely. Plastic waste stuck in mangroves can also block the sunlight that mangroves need to grow even though the functions of mangroves are essential, such as preventing erosion, and abrasion, shelter for some biota, and many more. Based on this background, researchers wanted to know the effect of plastic waste on the abundance of mangrove seedlings. This study aimed to determine the effect of plastic waste cover on the growth of mangrove seedlings and the impact of plastic waste on the abundance of mangrove seedlings in Tambak Wedi Surabaya. The method used was sampling vegetation on a transect measuring 2x2 m for seedlings, 5x5 m for saplings, and 10x10 m for trees at different locations and calculating the area covered by plastic waste at each station. From the observations, data obtained at each station showed that the plastic waste covering the mangrove area, the amount of plastic waste at each station was 139.4 – 144.6 m2, the density of mangroves at three stations was 14,700 ind/ha, and for the average density of seedlings at each station of 26,666 ind/ha. When viewed from the standard criteria for mangrove damage, the density of mangrove seedlings in the Wedi Pond area is quite good.